1994
DOI: 10.1111/j.1699-0463.1994.tb04862.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunological study of chloralkali workers previously exposed to mercury vapour

Abstract: Several animal studies have suggested that exposure to inorganic mercury compounds may have effects on the immune system. Human data are, however, relatively sparse. The presence of several autoantibodies and the concentration of immunoglobulins and complement components were determined in the present cross‐sectional study in 77 chloralkali workers previously exposed to mercury vapour and 53 age‐matched referents. The mean duration of exposure to mercury vapour was 7.9 years (range 1.1–36.2), and the exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…In this respect, the results are in accordance with those of others Cardenas et al 1993). There was no signi®cant increase of ANA or organ-speci®c autoantibodies in the exposed workers as compared with nonexposed controls, which is in accordance with previous studies (Langworth et al 1993;Ellingsen et al 1994). The higher prevalence of ANA in the control group is considered to be a random ®nding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this respect, the results are in accordance with those of others Cardenas et al 1993). There was no signi®cant increase of ANA or organ-speci®c autoantibodies in the exposed workers as compared with nonexposed controls, which is in accordance with previous studies (Langworth et al 1993;Ellingsen et al 1994). The higher prevalence of ANA in the control group is considered to be a random ®nding.…”
Section: Discussionsupporting
confidence: 91%
“…Two recent studies have shown a signi®cant increase of serum immunoglobulin (Ig) isotypes in Hgexposed workers as compared with controls (Bencko et al 1990;Querioz et al 1994). Ellingsen et al (1994) reported that Hg-exposed chloralkali workers, in whom the exposure had ceased 1±35 years before the examination, showed no signi®cant increase of autoantibodies or serum Ig concentrations as compared with the unexposed controls. Langworth et al (1992Langworth et al ( , 1993 found no increase of autoantibodies or elevated serum Ig levels in subjects with low exposure to Hg vapor.…”
Section: Introductionmentioning
confidence: 97%
“…Apparently, the immunoglobulin concentrations varied at both examin ations, as seen from the authors' figures, emphasizing the individual reactivity. Conflicting results have, again, been reported by Ellingscn et al [244], who failed to reveal any increased prevalence of autoantibodies or changes in immu noglobulins or complement components among mercuryvapour-exposed chloralkali workers.…”
Section: Effects O F Mercury On B-cell-mediatecl Immunitymentioning
confidence: 81%
“…One further study reported a decrease of IgA and IgG levels after long-term occupational exposure (Moszczynski et al 1990). In two other studies no differences in immune status was observed between exposed subjects and controls (Langworth et al 1992;Ellingsen et al 1994). Importantly, however, no previous study has explored the effects on IgG subclasses, and the finding of a relation with IgG should therefore be confirmed in other studies.…”
Section: Discussionmentioning
confidence: 79%